2021
DOI: 10.31219/osf.io/5yh4r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of The Introduction of Skin Diseases Based on Augmented Reality

Abstract: Indonesia is a tropical country that has high rainfall. Environmental conditions greatly affect health conditions in humans such as skin health examples. Many people are still confused to identify the skin disease they are suffering from. This has a negative impact on people's lives. In this research, an application is made that is useful for introducing and informing various types of skin diseases with the Convolutional Neural Network (CNN) algorithm and implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In a study using TRAMP mice, the downregulation of pro-inflammatory mediators such as signal transducer and activator of transcription-3, AKT and IKKa/b by UA decreased tumour growth and increased mouse survival rates. 64,65 These findings suggest that UA has a lot of potential as an anti-inflammatory drug.…”
Section: Other Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study using TRAMP mice, the downregulation of pro-inflammatory mediators such as signal transducer and activator of transcription-3, AKT and IKKa/b by UA decreased tumour growth and increased mouse survival rates. 64,65 These findings suggest that UA has a lot of potential as an anti-inflammatory drug.…”
Section: Other Factorsmentioning
confidence: 96%
“…In vivo tests on the prefrontal cortex of mice revealed that the UA significantly decreased levels of inducible nitric oxide synthase, COX‐2, IL‐1, IL‐6 and tumor necrosis factor, as well as advanced glycation end‐products and reactive oxygen species. In a study using TRAMP mice, the downregulation of pro‐inflammatory mediators such as signal transducer and activator of transcription‐3, AKT and IKKa/b by UA decreased tumour growth and increased mouse survival rates 64,65 . These findings suggest that UA has a lot of potential as an anti‐inflammatory drug.…”
Section: Therapeutic Potential Of Uamentioning
confidence: 97%